PERANCANGAN INTERIOR BENGKEL MODIFIKASI SEPEDA MOTOR DI DENPASAR, BALI (Jurnal iSpectrum, 2023)
The development of motorcycle modifications in Indonesia is in great demand by the public. The resulting improvement affects not only the number of modifications made by the modifier, but also the quality. This can be seen from the motorcycle modification competition held and the many innovations made by the modifiers. Initially, there were many individual participants, but gradually many clubs automotive Currently, there are many types of motorcycles with various models that are modified in accordance with developing trends. The desire to modify motorcycles led to the emergence of motorcycle workshops in Bali, especially in Denpasar. The emergence of this motorcycle modification workshop is very helpful for those who are not able to make their own modifications and need the services of others to fulfill their wishes through the workshop. Therefore, the development of the Interior Design of a Motorcycle Modification Workshop in Denpasar is expected to meet the needs of people who want to modify their motorbikes on a small or large scale in a convenient location, complete and integrated facilities. efficient in all respects in terms of time and materials, as well as creating new innovations to increase customer satisfaction and gain customer loyalty to help develop the world of motorcycle modification.